Root Transcriptome and Metabolome Profiling Reveal Key Phytohormone-Related Genes and Pathways Involved Clubroot Resistance in Brassica rapa L. - Wei, Xiaochun; Zhang, Yingying; Zhao, Yanyan; Xie, Zhengqing; Hossain, Mohammad Rashed; Yang, Shuangjuan; Shi, Gongyao; Lv, Yanyan; Wang, Zhiyong; Tian, Baoming; Su, Henan; Wei, Fang; et al. (Frontiers in Plant Science, 2021)
Plasmodiophora brassicae, an obligate biotrophic pathogen causing clubroot disease can seriously affect Brassica crops worldwide, especially Chinese cabbage. Understanding the transcriptome and metabolome profiling changes during the infection of P. brassicae will provide key insights in understanding defense mechanism in Brassica crops. In this study, we estimated the phytohormones using targeted metabolome assays and transcriptomic changes using RNA sequencing (RNA-seq) in the roots of resistant (BrT24) and susceptible (Y510-9) plants at 0-, 3-, 9- and 20 days after inoculation (DAI) with P. brassicae. Differentially expressed genes (DEGs) in resistant vs susceptible lines across different time points were identified. Co-Expression Network Analysis (WGCNA) of the DEGs revealed six pathways including ‘Plant-pathogen interaction’ and ‘Plant hormone signal transduction’ and fifteen hub genes including pathogenic type III effector avirulence factor gene (RIN4) and Auxin-responsive protein (IAA16) to be involved in plants immune response. Inhibition of IAA, CTK, JA and SA contents, and changes in related gene expression in R-line may play important roles in regulation of Clubroot Resistance (CR). Based on the combined metabolome profiling and hormone-related transcriptomic responses, we propose a general model of hormone mediated defense mechanism. This study will definitely enhance our current understanding and pave the way for improving clubroot resistance in Brassica rapa.